The Validity of Measures of Instructional Alignment With State Standards Based on Surveys of Enacted Curriculum. (June 2022) - Atchison, Drew; Garet, Michael S.; Smith, Toni M.; Song, Mengli
This paper uses a validity argument approach to examine the validity evidence for measures of instructional alignment based on an instrument adapted from the Surveys of Enacted Curriculum (SEC). Using the instrument, Grade 4 math and Grade 5 English language arts teachers reported the level of emphasis they gave to subject-specific topics and cognitive demands in their instruction, which provided the data for measuring instructional alignment—both overall and by topic and by cognitive demand—with state standards. We found that (a) teachers differentiated topics but not cognitive demands when reporting on the content of their instruction, (b) teachers likely overreported levels of emphasis on topics and cognitive demands, and (c) overall alignment and alignment by cognitive demand were not significantly associated with teachers' value-added scores. Although this study examined a specific version of the SEC, we believe the findings apply more broadly to SEC-based measures of instructional alignment.